The burden of tuberculosis in patients with stage 5 chronic kidney disease undergoing dialysis therapy at Livingstone hospital, Port Elizabeth - Ndamase, Siviwe (Department of Medicine, 2020)
Background: Tuberculosis (TB) now ranks as the leading cause of death from a single infectious agent worldwide. Patients on dialysis are particularly vulnerable to TB infection due to immune dysfunction. Despite this, there is a paucity of incidence data on TB in dialysis patients in high burden settings such as South Africa. The aim of this study was to determine the incidence of TB in chronic kidney disease stage 5 patients on dialysis (CKD-5D) at a single centre in the Eastern Cape, South Africa and to identify risk factors associated with TB infection. Methods: We conducted a retrospective cohort study of all consenting prevalent CKD-5D patients between April 2010 and March 2014 at the Livingstone Tertiary Hospital Renal Unit in the Eastern Cape, South Africa. TB was defined as “definite” or “probable” according to WHO criteria. Results: One hundred and eleven patients were enrolled: they were predominantly black African (73%) and female (53%); mean age was 42 years (SD ±9years). The prevalence of HIV infection was 11%: all were on antiretroviral treatment and all had suppressed viral loads. Sixty eight patients were on haemodialysis (HD) and 43 patients were on peritoneal dialysis (PD). Nineteen patients were diagnosed with 20 episodes of TB; 14 cases were pulmonary and 6 cases extrapulmonary. Of the patients with TB, 2 were HIV infected. Of the 20 TB cases, 7 (35%) were definite TB cases and 13 (65%) had probable TB. The calculated incidence rate was 4505 per 100 000 patient years. Only informal housing and a history of hospitalization were significantly associated with a diagnosis of TB. Conclusion: Dialysis patients in the Eastern Cape region of South Africa are at extremely high risk for the acquisition of TB with an incidence rate that is 4.1 times that of the local Nelson Mandela Bay population and over 5 times that reported in the general population for the country as a whole. Only informal housing and a history of hospitalization were identified as positive risk factors in this young population with a low HIV prevalence. Isoniazid prophylaxis in this high risk group might be of benefit but further studies are required to inform such treatment.